TECHNOLOGICAL APPROACH TO THE HARMONIOUS DEVELOPMENT OF THE STUDENT'S PERSONALITY IN THE EDUCATIONAL PROCESS - THE DRIVING FORCE GROWTH OF TEACHER'S CREATIVE POTENTIAL (Pedagogy of Higher and Secondary Education, 2022)
This article deals with the harmonic development of a student’s personality with the help of technological approach in the process of studying the success of which is based on the pedagogical skill.
Keywords: harmonious development; technological approach; potential; adaptation; integration; leading qualities of a personality; personality formation stapes; pedagogical skill; professional qualities of a teacher; creative work areas; basic competence qualities of a man